2002
DOI: 10.1242/jcs.115.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The tubby-like proteins, a family with roles in neuronal development and function

Abstract: The identification of a mutation at the tubby (Tub) locus, which causes obesity and neurosensory degeneration, led to the discovery of the tubby-like proteins (TULPs). Tub and the genes that encode three tubby-like proteins (TULP1- TULP3) form a novel, small gene family that plays an important role in maintenance and function of neuronal cells during development and post-differentiation. Although exploration of the molecular function of these genes is still in its infancy, recent biochemical studies have provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…TUB (TUB Bipartite Transcription Factor) and SCP2 have been studied in individuals with neuronal disorders [ 35 , 36 ]. TUB is part of the Tubby signaling pathways that are important during neurodevelopment [ 37 ]. A TUB frameshift mutation in three siblings was associated with retinal dystrophy and obesity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…TUB (TUB Bipartite Transcription Factor) and SCP2 have been studied in individuals with neuronal disorders [ 35 , 36 ]. TUB is part of the Tubby signaling pathways that are important during neurodevelopment [ 37 ]. A TUB frameshift mutation in three siblings was associated with retinal dystrophy and obesity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, five mammalian tubby-like proteins ( TULPs) family members (TUB, TULP1, 2, 3 and 4) have been identified with an important role in the maintenance of the central nervous system [15]. The TULPs are characterized by a unique "tubby domain" of ~260 amino acid residues in the C-terminal [31], which forms a central hydrophobic α-helix transversing the β-barrel structure [9].…”
Section: Discussionmentioning
confidence: 99%
“…The 'tubby domain' contains a phosphatidylinositol-binding region specifically binding to phosphatidylinositol 4,5-bisphosphate (PIP2) [8] and a DNA-binding domain (DBD) that selectively binding to double-stranded DNA [9]. Although the N-terminal motifs of the TULPs are poorly conserved [32], the C-terminal "tubby domains" of the TULPs are remarkedly conserved with 55-95% identity across species from plants to humans [15], implying an evolutionarily conserved function [9]. Structure-function analysis by Sunshin Kim et al [24] demonstrated that the tubby domain in Tub plays a crucial role in its subcellular localization and its solubility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) In the MEXP2780 sample data, patients who had low TULP3 expression levels exhibited a 3.4 times greater chance of survival compared to those who had high expression levels and a difference between the two expression groups of p-value = 0.00496. plays an essential role during mammalian development, since mutations in TULP3 exhibit embryonic lethality with defects during neural tube closure. [30][31][32] The tubby domain is positively charged at the carboxy-terminal region and possesses a nuclear localization conserved sequence, which enables its role as a transcription factor. This region of the TULP3 protein binds to the plasma membrane, specifically to phosphatidylinositol-4,5bisphosphate (PIP 2 ), a phospholipid highly enriched in the membrane.…”
Section: Discussionmentioning
confidence: 99%